THE REPRODUCTIVE CHARACTERISTICS OF GAYO BUFFALOES AS A LOCAL LIVESTOCK GENETIC RESOURCE IN THE MESIDAH SUBDISTRICT, BENER MERIAH REGENCY - Mohd. Agus Nashri Abdullah; Tudung Mulie Gundala; Eka Meutia Sari (Universitas Syiah Kuala, 2022)
This research aimed to identify the reproductive characteristics of Gayo buffaloes in the Mesidah Sub-district, Bener Meriah Regency. There were three locations of the current study namely Perumpaken Benjadi, Wer Tingkem, and Simpur, which were determined using the purposivesampling technique. A survey was used as the research method to obtain primary data and secondary data. Primary data were collected throughdirect interviews with buffalo livestock owners. They were asked a set of questions that had been prepared in a questionnaire. Secondary datawere obtained from related agencies in Bener Meriah Regency. The number of respondents was 92 from four villages in the Mesidah Sub-district,Bener Meriah Regency. Breeders as respondents were selected using a purposive sampling method, with minimum requirements that they hadraised two buffaloes that had given birth more than once and that the breeders had at least four years of farming experience. The research datawere analyzed using descriptive statistic. The results showed that the Gayo buffaloes in the Mesidah Sub-district, Bener Meriah Regency, had reproductive characteristics that met the standards. This can be seen from the obtained data which were almost the same as the average age of the reproductive characteristics of buffaloes in Indonesia. Gayo buffaloes in the Mesidah Sub-district experienced the first estrus (puberty) at 33.83 months old, first mating at 34.61 months old, and first calving at 45.29 months. The average gestation period was 10.51 months, the calving interval was 15.5 months, and the average service period was 3.66 months, while maintenance management was carried out extensively. Based on the results, it can be concluded that the reproductive characteristics of Gayo buffaloes in the Mesidah Sub-district, Bener Meriah Regency, still meet the standards. The average reproductive characteristics of Gayo buffaloes are generally the same as the average characteristics of other buffaloes in Indonesia.